Reduced tissue creatine levels in patients with long COVID-19: A cross-sectional study - Ranisavljev, M; Todorovic, N; Ostojic, J; Ostojic, SM (Journal of postgraduate medicine, 2023)
Total creatine concentration in the skeletal muscle and brain of long COVID patients were significantly lower when compared to the reference values for the general population, as measured with proton magnetic resonance spectroscopy at 1.5-T in vastus medialis muscle, thalamus, and three bilateral cerebral locations across the white and gray matter.